Effectiveness of Agricultural Tools and Machines (Alsintan) Assistance in Increasing Corn Production in Belu Regency, East Nusa Tenggara Province - Ridwan; Pambudi, Dhimas Eko; Gabrill, Rico Muhammad (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2025)
This study aims to analyze the effectiveness of agricultural machinery assistance (alsintan) in increasing corn production in Belu Regency, East Nusa Tenggara Province. Corn, as a key commodity, has experienced productivity fluctuations in recent years. The local government, through the Department of Agriculture and Food Security, has distributed various types of alsintan, such as tractors, corn planters, and power threshers, to improve farming eficiency. This research uses a qualitative approach with a phenomenological method. Data were collected through in-depth interviews, observations, and documentation. The results of the study indicate that the assistance of alsintan is effective in accelerating planting and harvesting processes and reducing reliance on manual labor. However, the effectiveness of this assistance is influenced by training, inter-agency cooperation, and limited infrastructure. This study recommends enhancing continuous training for farmer groups to optimize the use of alsintan.